MAPK kinase 10.2 promotes disease resistance and drought tolerance by activating different MAPKs in rice. (5th October 2017) - Ma, Haigang; Chen, Jie; Zhang, Zhenzhen; Ma, Ling; Yang, Zeyu; Zhang, Qinglu; Li, Xianghua; Xiao, Jinghua; Wang, Shiping
Summary: Mitogen‐activated protein kinase (MAPK) cascades, with each cascade consisting of a MAPK kinase kinase (MAPKKK), a MAPK kinase (MAPKK) and a MAPK, have important roles in different biological processes. However, the signal transduction in rice MAPK cascades remains to be elucidated. We show that the structural non‐canonical MAPKK, MPKK10.2, enhances rice resistance to Xanthomonas oryzae pv. oryzicola ( Xoc ), which causes bacterial streak disease, and increases rice tolerance to drought stress by phosphorylating and activating two MAPKs, MPK6 and MPK3, respectively. MPKK10.2 ‐overexpressing (oe) plants showed enhanced resistance to both Xoc and drought, whereas MPKK10.2 ‐RNA interference (RNAi) plants had increased sensitivity to both Xoc and drought. MPKK10.2 physically interacted with MPK6 and MPK3, and phosphorylated the two MAPKs in vivo . Transcriptionally modulating MPKK10.2 influenced MPK6 phosphorylation during rice‐ Xoc interaction, and MPKK10.2 ‐oe/ MPK6 ‐RNAi double mutants showed increased sensitivity to Xoc . MPKK10.2 ‐oe/ MPK3 ‐RNAi double mutants showed survival rates similar to those of control plants, although the survival rates of MPKK10.2 transgenic plants changed after drought stress. These results suggest that MPKK10.2 is a node involved in rice response to biotic and abiotic responses by functioning in the cross‐point of two MAPK cascades leading to Xoc resistance and drought tolerance. Significance Statement: Mitogen‐activated protein kinase (MAPK) cascades play important roles in different biological processes. However, the signal transduction in rice MAPK cascades remains to be elucidated. Here we show that a MAPKK, MPKK10.2, increases rice resistance to bacterial streak disease and drought tolerance by phosphorylating and activating two MAPKs, MPK6 and MPK3, respectively, suggesting that MPKK10.2 is a cross point between rice response to biotic and abiotic responses.